Tumor necrosis factor receptor‐ associated factor 6 (TRAF6) regulation of development, function, and homeostasis of the immune system. Issue 1 (July 2015) - Walsh, Matthew C.; Lee, JangEun; Choi, Yongwon
Summary: Tumor necrosis factor receptor (TNFR)‐associated factor 6 (TRAF6) is an adapter protein that mediates a wide array of protein–protein interactions via its TRAF domain and a RING finger domain that possesses non‐conventional E3 ubiquitin ligase activity. First identified nearly two decades ago as a mediator of interleukin‐1 receptor (IL‐1R)‐mediated activation of NFκB, TRAF6 has since been identified as an actor downstream of multiple receptor families with immunoregulatory functions, including members of the TNFR superfamily, the Toll‐like receptor (TLR) family, tumor growth factor‐β receptors (TGFβR), and T‐cell receptor (TCR). In addition to NFκB, TRAF6 may also direct activation of mitogen‐activated protein kinase (MAPK), phosphoinositide 3‐kinase (PI3K), and interferon regulatory factor pathways. In the context of the immune system, TRAF6‐mediated signals have proven critical for the development, homeostasis, and/or activation of B cells, T cells, and myeloid cells, including macrophages, dendritic cells, and osteoclasts, as well as for organogenesis of thymic and secondary lymphoid tissues. In multiple cellular contexts, TRAF6 function is essential not only for proper activation of the immune system but also for maintaining immune tolerance, and more recent work has begun to identify mechanisms of contextual specificity for TRAF6, involving both regulatory protein interactions, and messenger RNA regulation by microRNAs.